Regulatory Role of Voltage-Gated Na+ Channel β Subunits in Sensory Neurons - Chahine, Mohamed; O'Leary, Michael E. (Frontiers in Pharmacology, 2011)
Voltage-gated Na+ channels are transmembrane-bound proteins incorporating aqueous conduction pores that are highly selective for Na+. The opening of these channels results in the rapid influx of Na+ ions that depolarize the cell and drive the rapid upstroke of nerve and muscle action potentials. While the concept of a Na+-selective ion channel had been formulated in the 1940s, it was not until the 1980s that the biochemical properties of the 260-kDa and 36-kDa auxiliary β subunits (β1, β2) were first described. Subsequent cloning and heterologous expression studies revealed that the  subunit forms the core of the channel and is responsible for both voltage-dependent gating and ionic selectivity. To date, ten isoforms of the Na+ channel α subunit have been identified that vary in their primary structures, tissue distribution, biophysical properties, and sensitivity to neurotoxins. Four β subunits (β1-β4) and two splice variants (β1A, β1B) have been identified that modulate the subcellular distribution, cell surface expression, and functional properties of the α subunits. The purpose of this review is to provide a broad overview of β subunit expression and function in peripheral sensory neurons and examine their contributions to neuropathic pain.